Artificial Intelligence Through Games for Early Childhood (Case Study: Kindergarten School) - Dina Fadiyah; Yonarisman Muhammad Akbar (Universitas Islam Darul Ulum Lamongan, 2024)
This paper intends to see how the development of technology is increasing rapidly until it has penetrated into the world of education, where learning can now be done through games. In the past, games were only known as play tools, solely for entertainment and had no educational elements. But now, games are often used by young children as a learning method and this has been implemented in various schools, especially international schools. In this study, the focus that will be translated is how artificial intelligence through games can increase intelligence and stimulate children in terms of learning. By using qualitative methods with case study studies, it is hoped that this study can add insight to all of us as academics so that we are more open to thoughts and literate about technology which is currently very sophisticated.